Longitudinal trends in vaping, smoking, and harmful alcohol use across sexual orientations in the UK (2014–2021) - Yihong Bai; Peiya Cao; Chungah Kim; Kristine Ienciu; Gwen Ehi; Antony Chum (PLoS ONE, 2026)
Background Sexual minorities, including lesbian, gay, and bisexual individuals, often face higher substance use rates due to societal stressors. Recent societal changes, including the COVID-19 pandemic and rising hate crimes in the UK, may have impacted these disparities across sexual orientations. This study aims to examine changes in vaping, smoking, and alcohol use disparities across sexual orientations in the UK from 2014 to 2021. Method Data from the UK Longitudinal Household Survey (2014–2021) were analyzed, covering 42,052 participants aged 16 + . Sexual orientation categories included heterosexual, gay/lesbian, bisexual, and other sexual minorities. The outcomes were smoking, vaping, and harmful alcohol drinking. Longitudinal logit models with generalized estimating equations were used, adjusting for demographic factors. Predictive prevalences were calculated and used to examine the disparities between each sexual minority group and the heterosexual group over time. Results We did not find consistent increases in substance use disparities across sexual orientation groups in the UK from 2014 to 2021. Small differences were observed among bisexual individuals who had a higher predicted prevalence of harmful alcohol drinking in 2019–2020 (~11–13% higher), while gay/lesbian individuals showed higher vaping prevalence in 2019 (~5% higher) than heterosexual individuals. For smoking, no disparities were observed. Conclusion Unlike prior studies that reported disparities, our longitudinal analysis found little to no evidence that sexual minorities had elevated or widening substance use disparities. While some subgroups exhibited elevated risks in specific years, these patterns were not sustained over time. Future research should explore how social stressors, policy contexts, and community norms interact to inform targeted, inclusive interventions that reflect the diversity within LGBTQ+ populations.